Performance analysis of ad hoc on-demand distance vector routing protocol under the real world implementation and simulation environment / Yusnani Mohd Yussoff - Mohd Yussoff, Yusnani (2007)
Ad Hoc networks have become increasingly important in view of their promise of ubiquitous connectivity beyond traditional wired infrastructure networks. Such networks, consisting of potentially highly mobile nodes, have provided new challenges by introducing special considerations stemming from the unique characteristics of the wireless medium and the dynamic nature of the network topology. This research was conducted with the objective of studying the performance of Ad Hoc wireless networks; the area of which currently falls under emerging technologies in the Wireless Communication. The study involved two major works; real world implementation and simulation of the Ad Hoc network. Both works used Ad Hoc OnDemand Distance Vector (AODV) as the routing protocol. The real world implementation was carried out in the Wireless Laboratory at Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam where a test bed of Ad Hoc network consists of four static nodes was set up. All tests and data collection on the real world implementation were done using various traffic monitoring and measurement software. Performance parameters used in both studies are throughput, Round Trip Time (RTT) and packet loss rate. The performance was studied by varying the number of hops in the Ad Hoc communication while distance between nodes and node mobility were kept constant. A simulation study on the same network topology was subsequently carried out using JSim network simulation software. J-Sim is an open source and component based simulation software and was entirely developed in Java. J-Sim components are autonomous and are realization of software ICs. To ensure valid and comparable data between simulation and real world implementation, the network topology, components and model used in the simulation was modified to be as close as possible to the real world implementation specification. The Free Space Model available in J-sim was used to model the radio propagation wave in the laboratory environment. This model assumes that no obstacle that can degrade the signal strength of the wireless cards on the Ad Hoc nodes as all the nodes in the laboratory were located in the same room.